O GENE DA ENZIMA CONVERSORA DE ANGIOTENSINA E SUAS VARIANTES GENOTIPICAS EM HIPERTENSOS E NORMOTENSOS - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2013)
High blood pressure (HBP) is a multifactorial clinical condition characterized by high and sustained levels of blood pressure (BP). The renin-angiotensin system is involved in the control of the BP, and has as a component the angiotensin converting enzyme (ACE). Recent studies that relate gene variants of Angiotensin Converting Enzyme (ACE) gene, increase the risk of hypertension, compared with the presence of the allele D. Thus, it becomes necessary studies aimed at investigating the relationship of the polymorphism in intron 16 of the ACE gene with hypertension. The aim of the study was to verify the relationship between I / D polymorphism of the ACE gene and genotypic variants with the installation of HBP in four distinct groups. Participants were 112 individuals arranged in the following groups: normotensive (control), hypertensive and non-obese, hypertensive and obese and hypertensive and with type II diabetes mellitus. We evaluated the possible relationship between I/D polymorphism of the ACE gene in different groups of hypertensive patients, but there was no significant difference between the genotypes in different groups in the sample. Regarding the epidemiology higher the body mass index (BMI), waist circumference, triglycerides and cholesterol levels and physical inactivity, was greater incidence of hypertension in the population. The data obtained in this study reinforce environmental interference that are prevalent in the evolution of the framework of HBP and not related to the frequency of the D allele in the population studied.
Keywords: Hipertensão arterial sistêmica; gene da eca; polimorfismo I/D; High blood pressure; ACE gene; I/D polymorphism; CNPQ::CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOLOGIA MOLECULAR